New intra-body sensor for E-Health applications - Garcia, João Filipe Roxo (2015)
Sensor nodes are small devices able to collect and retrieve sensorial data. The use of these sensors for medical purposes offers valuable contributions to improve patients‟ healthcare, both for diagnosis and therapeutics monitoring. An important and common parameter used in healthcare diagnosis is body temperature. It is monitored on several matters related with gynaecological and obstetrics issues but, usually it is measured at the skin‟s surface. Thus, this dissertation proposes the design concepts of a new intra-body sensor for long-term intra-vaginal temperature collection. The embedded IEEE 802.15.4 communication module allows the integration of this sensor in wireless sensor networks for remote data access and monitoring. It is presented the sensor architecture, the construction of the corresponding testbed, and its performance evaluation. This sensor may be used in several applications, including fertile and ovulation period detection, and preterm labor prevention. The features of the constructed testbed were validated in laboratory field verifying their accuracy and performance.